A novel approach to seabird posture estimation: finding roll and yaw angles of dynamic soaring albatrosses using tri-axial magnetometers - Rory Wilson (Royal Society Open Science, 2023)
With advances in bio-logging technology, the posture of animals is now commonly described by inertial measurement units, which include tri-axial accelerometers to estimate pitch and roll angles. Many large seabirds use dynamic soaring flight to travel long distances, but this low-cost flight mode results in high centripetal acceleration, which obscures posture derived from accelerometers. Tri-axial magnetometers are not influenced by acceleration and might provide a way to estimate the posture of animals that experience high centripetal acceleration. We propose a new method to estimate the posture of dynamic soaring seabirds using tri-axial magnetometer data, with the assumption that they do not have large pitch angles during routine flight. This method was field-tested by deploying a combination of bio-logging devices on three albatross species breeding on Marion Island, using bird-borne video loggers to validate the roll angles. Validated data showed that the method worked well in most instances, but accuracy decreased when the heading was close to magnetic north or south. Accurate, fine-scale posture estimates may provide insight into dynamic soaring flight and allow estimates of fine-scale tracks using dead-reckoning, not only for seabirds, but potentially for other species where centripetal acceleration limits the use of accelerometers to estimate posture.